The comparison to the characteristics of three-dimensional joint kinetics between single leg and double leg rebound jump - Kariyama, Y.; Fujii, H.; Mori, K.; Zushi, K. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to clarify the differences between the SRJ and DRJ in terms of three-dimensional joint kinetics for the takeoff leg. Twenty male track and field athletes were performed repeated rebound jump with single leg (SRJ) and double leg (DRJ). Kinematics and kinetics data were recorded using Vicon T20 system (250 Hz) and force platforms (1000 Hz). When comparing a SRJ to a DRJ, the characteristics of the former are as follows: 1) the jump height by a single leg is significantly higher because of the larger hip joint work around the extension-flexion, especially on the abduction-adduction axes; 2) the hip extension and abduction torque is larger; and 3) in the SRJ, the hip abduction torque is larger than the hip extension torque. Therefore, the joint kinetics of the SRJ is characterized by the large hip abduction torque, in addition to the large hip extension torque.